BROSUR BERTEMA POP-UP SEBAGAI MEDIA PROMOSI MUSEUM GUNUNG MERAPI YOGYAKARTA - , RACHMAT TEGUH WIDIANTORO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Growth and development of the tourist attraction in followed and driven by the community at large. One of the easiest marketing technique is through brochure. Today many tourist need brochures for their travel guides. Because brochures are one of the easiest medium in which to get to know some information from this attractions. But in reality in Indonesia, it is difficult to get a brochures for tourist in places that are the gate of the travel destinations like airport, bus station, train station and harbour. And attractions that exist in Indonesia, also encountered the same difficulty to get a brochures. From the number of brochures that has no availability in all kind of brochures. Based on the description that has been described above, the promotion is a step that is important for the progress and the development of tourist destinations. And media campaigns are most easily created is by brochures, but in Indonesia to get a brochure themed tourist destinations is so difficult because of there are minimal like them. The promotion of tourist destinations in indonesia should continue to grow, including brochures and flyers. But not like any usual brochures and conventional concept but brochures with Pop Up themed. The inside of the brochure will be given any informations about tourist destinations and visualization of the tourist destinations, so itâs more interesting to look at it and read by the tourist. Museum Volcano of Yogyakarta as one of tourist destination in indonesia should continue to develop its promotion. Pop Up brochure can be an alternative which also became souvenirs to give to every tourist who visti there